OXYGEN ISOTOPIC DISTRIBUTION IN AN AMOEBID OLIVINE AGGREGATE FROM THE ALLENDE CV CHRONDITE: PRIMARY AND SECONDARY PROCESSES - Imai H.; Yurimoto H. (My University, 2003)
The oxygen isotopic distribution in an amoeboid olivine aggregate (AOA), TTA1-02, from the Allende CV3 chondrite has been determined by secondary ion mass spectrometry. The irregular shaped TTA1- 02 (5×3mm) consists mostly of olivine grains of ca. 5μm in diameter. Olivine grains of Mg-rich (Fo95) and Fe-rich (Fo60) composition are in direct contact with each other, with a sharp compositional boundary. Oxygen isotopic compositions of Fe-rich olivine grains are 16O-poor (Δ17O ≅ −5‰), whereas Mg-rich olivine is 16O-rich (Δ17O ≅ −25‰). Several Al-rich inclusions (<ca. 500 μm in diameter) are enclosed by olivine grains in the AOA. Oxygen isotopic compositions of spinel and fassaite in Al-rich inclusions are 16O-rich (Δ17O ≅ −20‰), whereas those of anorthite, nepheline and phyllosilicate are 16O-poor (Δ17O ≅ −5‰). We propose the following sequence of events during the formation of AOAs in the Allende meteorite: 1) Formation of Al-rich inclusions with 16O-rich oxygen isotopic composition; 2) Accretion of Mg-rich olivine grains with 16O-rich oxygen isotopic composition around Al-rich inclusions; 3) Accretion into parent body; and 4) Aqueous alteration in the parent body, which led to crystallization of 16O-poor minerals, Fe-rich olivine, anorthite, nepheline, and phyllosilicate. This is reflecting reactions among primary 16O-rich AOA minerals and aqueous fluid having 16O-poor oxygen isotopic composition. Fe-rich olivine grains precipitated from aqueous fluids, which partially dissolved pre-existing Mg-rich olivine grains. Sintering and Mg-Fe diffusion occurred during thermal metamorphism. Anorthite, nepheline and phyllosilicate in Al-rich inclusions replaced primary anorthite or melilite during the aqueous alteration stage.